2013
DOI: 10.1371/journal.pone.0054808
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis and Genomic Organization of Major DNA Satellites in Banana (Musa spp.)

Abstract: Satellite DNA sequences consist of tandemly arranged repetitive units up to thousands nucleotides long in head-to-tail orientation. The evolutionary processes by which satellites arise and evolve include unequal crossing over, gene conversion, transposition and extra chromosomal circular DNA formation. Large blocks of satellite DNA are often observed in heterochromatic regions of chromosomes and are a typical component of centromeric and telomeric regions. Satellite-rich loci may show specific banding patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 72 publications
(108 reference statements)
4
55
0
Order By: Relevance
“…They evolve more rapidly than genic sequences, and mobile genetic elements are considered as main contributors to interspecific divergence [Charlesworth et al, 1994;Piednoël et al, 2012;Novák et al, 2014]. Repetitive DNA sequences represent a good source of molecular markers including cytogenetic landmarks [Paesold et al, 2012;Čížková et al, 2013]. As previously shown, some repeats might be species-or even chromosome-specific and can be used as probes for FISH in karyotyping, providing new insights into the evolutionary origins of species [Hobza et al, 2006;Paux et al, 2006;Dodsworth et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…They evolve more rapidly than genic sequences, and mobile genetic elements are considered as main contributors to interspecific divergence [Charlesworth et al, 1994;Piednoël et al, 2012;Novák et al, 2014]. Repetitive DNA sequences represent a good source of molecular markers including cytogenetic landmarks [Paesold et al, 2012;Čížková et al, 2013]. As previously shown, some repeats might be species-or even chromosome-specific and can be used as probes for FISH in karyotyping, providing new insights into the evolutionary origins of species [Hobza et al, 2006;Paux et al, 2006;Dodsworth et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The intention here is not to make an extensive and rigorous review of the amount of each satellite DNA studied, partly because the data are not always available, but it can be stated that the genomic content of a satellite DNA can range from 0.1% of the FriSAT1 satellite DNA in several Fritillaria species or 0.3% of satellite DNAs within the genome in Musa [Hribová et al, 2010;Čížková et al, 2013] to 36% of FriSAT1 in F. falcate [Ambrožová et al, 2011]. The relative proportions that a satellite DNA represents in the different genomes are data that must be treated with caution, but it is clear that the amount of satellite DNA present in a genome may be partly responsible for the genome size.…”
Section: Satellite Dna a Family Of Sequences That Get On Well With Ementioning
confidence: 99%
“…In rice and maize, for example, all centromeres have different retrotransposon families [Nagaki et al, 2005;Bao et al, 2006]. Furthermore, retrotransposons are the main component of banana and some wheat centromeres [Čížková et al, 2013;Li et al, 2013].…”
Section: Plant Centromere and The Pericentromeric Regionmentioning
confidence: 99%
“…While the implication in previous studies (Heslop-Harrison & Schwarzacher, 2007;Howell, Newbury, Swennen, Whithers, & Ford-Lloyd, 1994;Nwakanma, Pillay, Okoli, & Tenkouano, 2003;Nair, Teo, & Schwarzacher, Heslop-Harisson, 2005) alluded marked differentiation of the A and B genomes, the SC3 primers developed in this study from the A genome do not suggest such a differentiation. Evidence for the lack of complete differentiation of the A and B genomes of banana does exist in the literature (Ortiz & Vuylsteke, 1994;Osuji, Harrison, Crouch, & Heslop-Harrison, 1997;D'Hont, Paget-Goy, Escoute, & Carreel, 2000;Khayat, 2004;Boonruangrod, Desai, Fluch, Berenyi, & Burg, 2008;Jeridi et al, 2011Jeridi et al, , 2012Cizkova et al, 2013;De Jesus et al, 2013). The first study that alluded to the lack of differentiation between the A and B genomes was that of (Nair, Teo, Schwarzacher, & Heslop-Harisson, 2005).…”
Section: Discussmentioning
confidence: 99%
“…In a subsequent study, Jeridi et al (2011) used cytogenetic evidence of mixed disomic and polysomic inheritance to suggest that there are chromosome exchanges between M. acuminata (AA) and M. balbisiana (BB). Cizkova et al (2013) used flow cytometry, ITS and SSR to support their hypothesis that recombination does occur between the A and B genomes of banana. Finally, the study by Jeridi et al (2012) on the organization of DNA satellites in banana showed that two satellites derived from M. acuminata were widespread in M. balbisiana and a number of ABB hybrids and the S genome.…”
Section: Discussmentioning
confidence: 99%